Knowledge management practice in organizations : the view from inside - De Stricker, Ulla (Information Science Reference, 2014)
"This book brings together industry experts to discuss the realities of knowledge management work in organizations, examining the challenges associated with operational knowledge management"--Resumé vydavatele
"Premier Reference Source"--Z obálky
Terminologický slovník
Keywords: znalostní management; implementace (management); knowledge management; implementation (management); sborníky; papers of several authors